Assessment of users’ expectations, perceived quality and satisfaction with primary care in Greece - Raftopoulos, Vasilios (My University, 2010)
Aim: To explore users’ expectations, their perceived quality and their satisfaction with primary care services an anonymous questionnaire has been administered to a sample of 212 users. Background: Patient satisfaction with quality of primary care is a dominant concept in quality assurance and quality improvement programs. Methods: It has been used the Expectations-Perceived Quality-Satisfaction with Primary Care Services Scale (E-PQ-SPCSS) that was developed and validated in this study. Data were analysed using SPSS, version 18. Results: The overall satisfaction with the primary care services was 97.2%, with the medical care provided was 95.3% and with nursing care was 92.5%. Nursing care was provided to 126 (59.4%) users. These users were more satisfied (p<0.0001) with global nursing care provided (4.52±0.70) than those who were not provided a nursing care intervention (3.53±1.73). Age correlated with global satisfaction with primary care (r=0.315, p<0.001) with medical (r=0.194, p<0.001) and nursing care (r=0.183, p<0.001) as well as with expectations total score (r=0.295, p<0.001), perceived quality of care total score (r=0.366, p<0.001) and satisfaction with care total score (r=0.207, p=0.002). Based on Cattell’s visual scree plot, four factors accounting for 64.34% of the item covariance were extracted and rotated through factor analysis (nurse’s technical and interpersonal competence, physician’s interpersonal competence, physician’s technical competence and structure characteristics).Conclusions: The psychometric properties of the E-PQ-SPCSS were good enough indicating that the scales are reliable and adequate for group comparisons.
Keywords: Primary care (Medicine); Patient satisfaction; Reliability; Medical care